The Relationship Of 'LILA' To The Incidence Of Anemia In Pregnant Women - Mona Lisa; Winnie Tunggal Mutika; Melda Maulia Herlisya; Ambariani Ambariani (Lambung Mangkurat University, 2023)
Anemia in pregnant women is the highest cause of maternal mortality, with 40% of pregnant women suffering from anemia. Maternal health during the pre-pregnancy period, during pregnancy, and during breastfeeding is a very critical period for the growth and development of the child. The first 1000 days of life is a sensitive period or